Evaluasi Pelaksanaan Pemberdayaan Perempuan Melalui Program Desa Prima Di Desa Karangsari, Kulon Progo, DIY - Ismiasih, Ismiasih; Purwandari, Istiti; Stone, Evander (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2024)
The poverty rate in the Special Region of Yogyakarta (DIY) according to data from the Central Bureau of Statistics (BPS) was recorded at 11.49%. Women's empowerment programs have an important role in advancing society and the economy as a whole. The Special Region of Yogyakarta Provincial Government reduces poverty through the optimization of the Desa PRIMA Program (Perempuan Indonesia Maju Mandiri). The Desa PRIMA program aims to improve community welfare by increasing productivity and participation of all communities, especially women, and helping to improve the quality of life of the community in general. This study is using qualitative descriptive method. The sampling method is carried out using census sampling.Â The types of data sources used are primary and secondary data sources. The results showed that: 1)The implementation of empowerment activities carried out has 2 approaches, namely the Top-Down approach, and also the Bottom-Up. Based on observations, the Top-Down approach is the majority method used; 2)The evaluation results show that the Desa PRIMA program in Karangsari Village received a very good overall assessment with score 2,86, indicating that the planning, implementation, process, and results of this program have been implemented well.